Reimagining Work–Family Balance and Psychological Well-Being of Working Mothers: A Post-Pandemic Systematic Review - Badi'atul husna; Ika Andrini Farida; Hanggara Budi Utomo (Jurnal Psikologi dan Konseling West Science, 2025)
Balancing work and family demands is a major challenge for working mothers with preschool-aged children, affecting their psychological well-being and quality of childcare. This study aims to systematically review the relationship between work-family balance (WFB), psychological well-being, and the mediating and moderating factors involved. Employing a Systematic Literature Review (SLR) approach following PRISMA 2020 guidelines, 10 empirical articles were selected from an initial pool of 250 based on strict inclusion criteria. The studies focused on working mothers with children aged 0-6 years across diverse cultural and occupational contexts, using quantitative survey designs. Narrative thematic analysis synthesized the findings. Results reveal that WFB significantly enhances psychological well-being, mediated by satisfaction of basic psychological needs (autonomy, competence, relatedness), and moderated by social support and workplace flexibility which strengthen this relationship. The novelty of this study lies in its cross-cultural integration and contextualization in the post-pandemic era, highlighting psychological and structural mechanisms as a foundation for interventions. Practical implications emphasize the necessity for family-friendly workplace policies and psychological interventions tailored to individual needs to support working mothers’ well-being and productivity.